A DNA-mimic contact-active functional group for antifouling ultrafiltration membranes. (February 2019) - Wang, Xinbo; Cheng, Hong; Hong, Peiying; Zhang, Xixiang; Lai, Zhiping
Abstract: Despite advanced materials and techniques to reduce the fouling issue of membranes, 10–30% of the cost of ultrafiltration (UF) processes have been spent on membrane cleaning. Particularly in water treatment, the traditional heavy metal-based method is challenged due to its environmental pollution risk and increasing public health awareness. Here, we report the synthesis of a metal-free contact-active antifouling and antimicrobial membrane by covalently functionalizing a commercial polyacrylonitrile (PAN) UF membrane with 2, 4-diamino-1, 3, 5-triazine (DAT) via a one-step catalyst-free hydrothermal [4 + 2] cyclization of dicyandiamide reaction. The proposed mechanism of the antimicrobial activity of the DAT-functionalized membrane is through strong attraction between the DAT groups and the microbial membrane protein via strong hydrogen bonding, leading to microbial membrane disruption and thus microbe death. A high water flux and good reusability of the membrane against protein in a UF experiment were achieved. The low cost, easy availability of the compounds, as well as the facile reaction offer a high potential of the membrane for real applications in ultrafiltration. Highlights: A DNA-mimic group DAT is used as a novel antimicrobial agent. A DAT-PAN UF membrane is prepared by an easy surface reaction. The DAT-PAN membrane showed contact-active anti-biofouling. Novel contact active model of hydrogen bonding is proposed. High flux recovery ratio is obtained.